PERTANGGUNG JAWABAN PIDANA KORPORASI DALAM TINDAK PIDANA ILEGAL FISHING - Dukomalamo, Muhammad Jufri (Faculty of Law, Khairun University, 2025)
This research analyzes corporate criminal liability in illegal fishing in North Maluku. North Maluku, which has abundant fisheries resources, is closely related to illegal fishing crimes corporations commit. This not only causes economic losses but also covers comprehensive ecological aspects. Using qualitative methods with an empirical normative approach, this research found that illegal fishing crimes can be categorized into 2, namely administratively illegal and procedurally illegal. Through analysis carried out on two court decisions, namely Supreme Court Decision Number 72/Pid.Sus/2021/PN Tte, and Supreme Court Decision Number 275/Pid.Sus/2019/PN Tte, it was found that the person delegated responsibility by the court was the ship's captain. In fact, if further analysis is carried out, the criminal acts committed in these two cases have the potential to take the form of corporate crimes. The absence of a special judicial institution in the field of illegal fishing, as well as the law enforcement process which is still oriented towards humans (natuurlijke persoon) rather than legal entities (rechtspersoon) as legal subjects, are empirical obstacles why corporate accountability in illegal fishing crimes is difficult to implement.